QUALITY EDUCATION IN INDIA (International Journal of Food and Nutritional Sciences, 2021)
Quality is not related to cost, and adjectives or descriptors such as "high" and "poor" are not applicable. Consciousness and having different meanings, among many of them some of them are as per the Random House dictionary, is 1) awareness of one’s own thoughts feelings, and surroundings, 2) the full activity and engagement of the senses, and 3) the thoughts and feelings of individuals and groups.From reviewing the literature, one can find that there are four elements that contribute to developing awareness, finding alignment, and focusing attention. These are Action, Reflection, Interaction, and Education. In this regard the present study is to glace a lion note on role of Teachers and Parents in providing Quality Education in India.